Are the palms Washingtonia filifera and Chamaerops humilis suitable hosts for the red palm weevil, Rhynchophorus ferrugineus (Col. Curculionidae)? - Dembilio, Óscar; Jaques, Josep A.; Llácer, Elena (2017)
The red palm weevil, Rhynchophorus ferrugineus (Olivier) (Coleoptera, Curculionidae), is a widely distributed pest which has recently become the major pest of palms in the Mediterranean Basin. This weevil has been recorded on 19 different palm species, however, the host status of Washingtonia filifera and Chamaerops humilis remains unclear. The present study was carried out to check whether these species had either antixenotic or antibiotic mechanisms of resistance against this pest. Our results show that both W. filifera and C. humilis are resistant to R. ferrugineus. Resistance in W. filifera is based on antibiosis whereas in C. humilis resistance is based on antixenosis.